The Impact of Brand Management, Consumer Trust, Emotional Branding, Customer Perceived Value, and Digital Communication on Market Performance - Dr. Shahid Nadeem (Indus Journal of Social Sciences, 2026)
In the modern competitive business environment, organizations increasingly focus on brand management strategies, emotional branding, digital communication, and customer relationship practices to strengthen consumer trust and improve market performance. Strong brands not only influence customer purchasing decisions but also contribute significantly to customer loyalty, organizational reputation, and sustainable competitive advantage. The present study examined the impact of brand management, consumer trust, emotional branding, customer perceived value, and digital communication on market performance among business organizations operating in highly competitive consumer markets. A quantitative correlational research design was employed to investigate the relationship between the independent variables and dependent variable. Data were collected from 320 consumers, marketing professionals, and business managers through structured self-administered questionnaires using a convenient sampling technique. The collected data were analyzed using descriptive statistics, Pearson correlation analysis, and regression analysis through the Statistical Package for Social Sciences (SPSS). The findings revealed that brand management significantly positively influenced consumer trust and market performance. Emotional branding also demonstrated a strong positive relationship with customer loyalty, customer engagement, and brand attachment. Similarly, customer perceived value positively affected customer satisfaction, repeat purchase intentions, and organizational competitiveness. Digital communication significantly enhanced customer interaction, brand awareness, and consumer relationships in online environments. The results further indicated that organizations implementing strong branding strategies and effective digital communication practices achieved higher market performance, customer loyalty, and brand competitiveness. The study highlights the importance of emotional connection, customer trust, digital marketing strategies, and value creation in improving organizational market performance. The findings may help marketing professionals, organizational leaders, and researchers better understand the strategic role of branding and digital communication in modern business environments. Future research should further examine the long-term impact of emotional branding and digital communication on customer behavior and organizational sustainability across different industries and cultural contexts.